(untitled) (International Journal of Banking and Finance, 2025)
In this contemporary era, mobile banking services enable customers to organise and accomplish cashless financial transactions using mobile devices. However, the general state of banks’ cybersecurity systems significantly impacts the usage of banking services offered through mobile networks among customers. The analysis was performed to assess how customers perceive the cybersecurity systems of banks and their association with mobile banking usage. By adopting a cross-sectional research design under the guidance of the Unified Theory of Acceptance and Use of Technology (UTAUT), the Partial least squares structural equation modelling (PLS-SEM) analysis reveals that banks’ cybersecurity systems’ performance expectancy had a significant positive impact on the use of mobile banking services. Further, banks’ cybersecurity systems’ effort expectancy, significant others’ comments and facilitating conditions significantly and positively influence bank customers to use mobile banking. Aligning with these findings, banks and financial institutions should prioritise and strengthen cybersecurity systems and simplify mobile banking processes for enhanced mobile banking adoption and usage among bank customers.